Effect of Yogic Practice on Selected Physical Fitness among Overweighted School Boys - K. Chandrasekaran2, T.P. Yokesh1* and (Recent Research in Science and Technology, 2011)
The objective of the study was to investigate the impact of yogic practice among overweighted school boys. To achieve this purpose, thirty overweighted school boys from various schools in Tiruchirappalli district were selected at random. Their age ranged between 14 and 17. The selected subjects were divided into two equal groups of 15 each, namely yogic practice group (group A) and control group (group B). The experimental group had undergone yogic practices for 12 weeks, five days a week. Whereas the control group (group B) maintained their daily routine activities and no special training was given. The subjects of the two groups were tested using standardized tests and procedures on selected physical variables before and after the training period to find out the training efforts in the following test items: BMI (body mass index) by measuring their height and weight of the subjects and flexibility by sit and reach box. The collected data were analyzed statistically through analysis of CoVariance (ANCOVA) to find out the pre and post training performances. To compare the significant difference between the adjusted final means and better group. The yogic practice group showed significant improvement due to 12 weeks of training on BMI and flexibility compared to control group.